Critical Review: Singapore: a 'NewAlexandria'of the Par East" dan " Cruel Temtation': A Case Study of a Korean Drama and its Reception in the Singaporean Community” - Dharwiyanto Putro, Bambang (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2021)
This paper was compiled inspired by two articles previously written by experts such as: Prof. Dr. Phil. I Ketut Ardhana, MA "Singapore: a 'NewAlexandria'of the Far East" in this book Tourism, Cultural Identity, and Globalization Singapore (2007), discusses a lot about Singapore from a historical perspective by seeing Singapore as a New Alexandaria country and the work of Kellie Chen " Cruel Temtation ': A Case Study of a Korean Drama and its Reception in the Singaporean Community "(2011). Next, a critical review will be carried out and an analysis of the contribution of Cultural Studies (its paradigm, its theoretical framework) to Singapore's development (Epistemology). Cultural studies (cultural studies) is an interdisciplinary or postdisciplinary field of inquiry that explores the production and cultivation of meaning maps as well as a discursive formation.